Embrace the Unexpected: How Organizations Foster Participatory Improvisation with Customers - Demetry, Daphne (Organization Science, 2025)
This study explores how organizations, together with their customers, solve problems in the face of disruptions, a process I call “participatory improvisation.” Drawing on interviews, ethnographic observations, and archival data collected from an underground restaurant, Secret Kitchen, and the theory of interaction order, I develop a process model of participatory improvisation with a two-part structure. First, I find that an organization must lay the foundation for participatory improvisation by establishing alternative conventions (e.g., expect and embrace the unexpected). Second, these conventions facilitate mutual face work by both the organization and customers in response to disruptions, thereby protecting interactions from breakdowns. When alternative conventions are not established, participatory improvisation may be ineffective, and interactions may be severely threatened. These findings contribute to the literature on organizational improvisation by uncovering how organizations can foster participatory improvisation and how it unfolds in situ. They also reveal an alternate way for customer-facing organizations to achieve their goals beyond routinization. Funding: This work was supported by the Ewing Marion Kauffman Foundation Dissertation Grant.